Acrylate polymer emulsion as well as preparation method and application thereof
By adding alkali-soluble bio-based resin and acrylate polymer to the aqueous polymer emulsion, the problem of poor adhesion on low-surface tension substrates is solved, and good adhesion and environmentally friendly coating formation are achieved.
Patent Information
- Application Number
- CN202410622032.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-20
- Publication Date
- 2025-04-15
AI Technical Summary
The existing aqueous polymer emulsions have poor adhesion on low-surface tension substrates, small contact area, and even cannot form a continuous coating, and the solvent-based polymer emulsions have a great pollution to the environment.
An acrylate polymer emulsion is provided, which comprises a water and resin composite composed of a mixture and/or a crosslinker formed of an alkali-soluble bio-based resin and an acrylate polymer, and improves the adhesion and stability of the emulsion by adjusting the component ratio and polymerization conditions.
A good bonding force is formed on a low-surface tension substrate, increasing the contact area, improving peel strength, and reducing environmental pollution.
Smart Images

Figure BDA0004847288770000131
Abstract
Description
Technical Field
[0001] The invention relates to an acrylic ester polymer emulsion and a preparation method and application thereof. Background Art
[0002] In daily life, a large number of materials are made of PP or PE, which have low surface tension. The existing technology often uses solvent-based polymer emulsions for coating as decorative coatings, but solvent-based polymer emulsions have a large impact on the environment. For example, solvent-based polymer emulsions often contain oily resins, which will lead to a large amount of VOC emissions, which is not conducive to the environment and human health.
[0003] Although the use of water-based polymer emulsions for coating is in line with the general trend of environmental protection, the water in the water-based polymer emulsion will shrink into a spherical shape on the surface of a substrate with low surface tension and cannot spread out to form a continuous coating.
[0004] Specifically, on substrates with low surface tension, aqueous polymer emulsions cannot wet well during coating due to their large surface tension, resulting in poor adhesion to the substrate, small contact area, and even failure to form a continuous coating. Summary of the invention
[0005] The present invention provides an acrylate polymer emulsion and a preparation method and application thereof to overcome the technical defects of the prior art, such as poor adhesion of aqueous polymer emulsion on low surface tension substrates, small contact area, and even inability to form a continuous coating. The present invention can enable the acrylate polymer emulsion to form good adhesion on low surface tension substrates and reduce environmental pollution.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides an acrylate polymer emulsion, which includes water and a resin composite, wherein the resin composite includes a mixture and / or a crosslinked product formed by an alkali-soluble bio-based resin and an acrylate polymer; wherein the content of each component is:
[0008] Water 40%-70%,
[0009] Alkali soluble bio-based resin 4%-15%,
[0010] Acrylate polymer 10.5%-65%;
[0011] The percentage is the percentage of each component to the total mass of the acrylic polymer emulsion;
[0012] The acrylic ester polymer comprises a repeating unit I corresponding to a non-fluorine-based vinyl monomer and a repeating unit II corresponding to a fluorine-based acrylic ester monomer, and the mass ratio of the repeating unit I to the repeating unit II is (10-60):(0.5-5).
[0013] In the present invention, for the cross-linked product formed by the alkali-soluble bio-based resin and the acrylate polymer, the content of the alkali-soluble bio-based resin and the content of the acrylate polymer represent the content of the part corresponding to the alkali-soluble bio-based resin and the part corresponding to the acrylate polymer in the cross-linked product, and it is not limited to the cross-linked product including the separate alkali-soluble bio-based resin and the separate acrylate polymer.
[0014] In the present invention, the non-fluorine-based vinyl monomer refers to a monomer that does not contain fluorine atoms; similarly, the fluorine-based acrylate monomer refers to a monomer that contains fluorine atoms.
[0015] In the present invention, the alkali-soluble bio-based resin meets compatibility and has both hydrophilic and lipophilic functional groups, and can be one or more of peach gum, shellac and sodium lignin sulfonate.
[0016] In the present invention, the non-fluorine-based vinyl monomer may be one or more of methyl methacrylate, acrylonitrile, butyl acrylate, isooctyl acrylate and styrene.
[0017] In the present invention, the fluorine-based acrylate monomer may be one or more of 2-fluoromethyl acrylate, perfluorohexylethyl methacrylate and perfluoroalkylethyl methacrylate.
[0018] In the present invention, the solid content of the acrylic ester polymer emulsion may be 35%-40%, such as 38.7% or 38.9%. The solid content refers to the mass percentage of solids in the acrylic ester polymer emulsion.
[0019] In the present invention, the viscosity of the acrylic polymer emulsion may be 280-320 mPa·s, such as 270 mPa·s or 301 mPa·s.
[0020] In the present invention, the average particle size of the acrylic polymer emulsion may be 75-85 nm, such as 77 nm or 83 nm.
[0021] In some specific embodiments, the alkali-soluble bio-based resin is peach gum, and the fluorine-based acrylate monomer is 2-fluoromethyl acrylate.
[0022] In some more specific embodiments, the alkali-soluble bio-based resin is peach gum, the fluorine-based acrylate monomer is 2-fluoromethyl acrylate; and the mass ratio of the peach gum to the repeating unit II is 30:(10-15).
[0023] In one embodiment, the alkali-soluble bio-based resin is peach gum, and the fluorine-based acrylate monomer is 2-fluoromethyl acrylate; the mass ratio of the peach gum to the repeating unit II is 30:14.
[0024] In some specific embodiments, the alkali-soluble bio-based resin is sodium lignin sulfonate, and the fluorinated acrylate monomer is perfluorohexyl ethyl methacrylate.
[0025] In some more specific embodiments, the alkali-soluble bio-based resin is sodium lignin sulfonate, and the fluorinated acrylate monomer is perfluorohexylethyl methacrylate; the mass ratio of the sodium lignin sulfonate to the repeating unit II is 30:(5-10).
[0026] In one embodiment, the alkali-soluble bio-based resin is sodium lignin sulfonate, and the fluorinated acrylate monomer is perfluorohexylethyl methacrylate; the mass ratio of the sodium lignin sulfonate to the repeating unit II is 30:6.
[0027] In a second aspect, the present invention provides a method for preparing an acrylic ester polymer emulsion, which comprises the following steps: subjecting a raw material to a polymerization reaction to obtain;
[0028] Wherein, the raw material includes the following components:
[0029] Alkali soluble bio-based resin 4%-15%;
[0030] Polymer monomer 10.5%-65%;
[0031] Water 40%-70%;
[0032] The percentage is the percentage of the mass of each component to the total mass of the raw material;
[0033] The polymer monomers include a non-fluorine-based vinyl monomer and a fluorine-based acrylate monomer, and the mass ratio of the non-fluorine-based vinyl monomer to the fluorine-based acrylate monomer is (10-60):(0.5-5);
[0034] During the polymerization reaction, the alkali-soluble bio-based resin is added all at once, and the polymer monomer and the water are added in batches.
[0035] In the present invention, the alkali-soluble bio-based resin can be one or more of peach gum, shellac and sodium lignin sulfonate.
[0036] In the present invention, the mass of the alkali-soluble bio-based resin may be 4.0%-5.0% of the total mass of the raw materials, for example 4.51% or 4.60%.
[0037] In some preferred embodiments, the alkali-soluble bio-based resin and water are added after forming a resin solution. The method for preparing the resin solution may include: mixing the alkali-soluble bio-based resin and water, heating, and stirring; wherein the heating temperature is preferably 70-80°C, the stirring speed is preferably 50-80r / min, and the stirring time is preferably 30-60min. The mass of water in the resin solution is included in the mass of water in the raw material.
[0038] In the present invention, the non-fluorine-based vinyl monomer may be one or more of methyl methacrylate, acrylonitrile, butyl acrylate, isooctyl acrylate and styrene.
[0039] In the present invention, the mass of the non-fluorinated vinyl monomer may be 30%-40% of the total mass of the raw materials, for example, 33.7% or 34.3%.
[0040] In the present invention, the fluorine-based acrylate monomer may be one or more of 2-fluoromethyl acrylate, perfluorohexylethyl methacrylate and perfluoroalkylethyl methacrylate.
[0041] In the present invention, the mass of the fluorine-based acrylate monomer may be 0.80%-3.00% of the total mass of the raw materials, for example, 0.90% or 2.14%.
[0042] In the present invention, the raw material may further include an emulsifier. The mass of the emulsifier may be less than 5% of the total mass of the raw material, for example, 0.77%-1.35%. The emulsifier may be added in batches.
[0043] Wherein, the emulsifier may be a non-fluorine emulsifier and / or a fluorine emulsifier. The fluorine emulsifier may be a perfluoroalkyl carboxylate and / or a perfluoroalkyl amide. The perfluoroalkyl carboxylate may be a sodium perfluoroalkyl carboxylate or a potassium perfluoroalkyl carboxylate. The perfluoroalkyl amide may be a perfluorooctane sulfonamide. The non-fluorine emulsifier may be one or more of sodium dodecyl polyoxyethylene ether sulfate, sodium dodecylbenzene sulfonate and OP-10. The mass of the fluorine emulsifier may be less than 2% of the total mass of the raw material. The mass of the non-fluorine emulsifier may be less than 3% of the total mass of the raw material.
[0044] In some preferred embodiments, the emulsifier is added in batches with the polymer monomer. Preferably, the polymer monomer, the emulsifier and water are added after forming a pre-emulsion. The preparation method of the pre-emulsion may include: mixing water, the polymer monomer and the emulsifier evenly and letting it stand. Preferably, the adding method is dropwise addition. The mass of water in the pre-emulsion is included in the mass of water in the raw material.
[0045] In the present invention, the raw material may further include an initiator. The initiator may be one or more of potassium persulfate, sodium persulfate, ammonium persulfate, hydrogen peroxide, ferrous sulfate, vitamin C and sodium pyrosulfite. The mass concentration of H2O2 in the hydrogen peroxide may be 7.5%-35%. The mass of the initiator may be 0.1%-3.0% of the total mass of the raw material. The initiator may be added in batches.
[0046] In some preferred embodiments, the initiator and water are added after forming an initiator solution, wherein the adding method is preferably dropwise addition. The mass of water in the initiator solution is included in the mass of water in the raw material.
[0047] In the present invention, the raw material may further include a chain transfer agent. The chain transfer agent may be one or more of 2-mercaptoethanol, thioglycolic acid, mercaptopropionic acid and isopropanol. The mass of the chain transfer agent may be 0.1%-3.0% of the total mass of the raw material, such as 0.12%-0.19%.
[0048] In the present invention, the temperature of the polymerization reaction can be selected according to the adaptability of the polymer monomer.
[0049] In some specific embodiments, the initial temperature of the polymerization reaction is 80-85°C, and the polymerization temperature is controlled to be 80-85°C during the polymerization reaction.
[0050] In some specific embodiments, the initial temperature of the polymerization reaction is 45-50°C, and the polymerization temperature is controlled not to be higher than 83°C during the polymerization reaction.
[0051] In the present invention, the "initial temperature of the polymerization reaction" refers to the temperature of the materials in the reactor before the polymer monomer is added.
[0052] In some specific embodiments, the raw material further includes a chain transfer agent, and the chain transfer agent may be added after the alkali-soluble bio-based resin is added.
[0053] In a preferred embodiment of the present invention, the polymer monomer is added in two batches, and the preparation method of the acrylic polymer emulsion may include the following steps:
[0054] S1, subjecting a first raw material to a first polymerization reaction; the first raw material comprises an alkali-soluble bio-based resin, a first batch of non-fluorine-based vinyl monomers, a first batch of fluorine-based acrylate monomers and a first batch of water;
[0055] S2, subjecting the second raw material to a second polymerization reaction; the second raw material comprises the reaction product of step S1, a second batch of non-fluorine-based vinyl monomers, a second batch of fluorine-based acrylate monomers and a second batch of water.
[0056] Further, the mass ratio of the alkali-soluble bio-based resin to the first batch of non-fluorine-based vinyl monomers may be 30:(15-16), such as 30:15.19 or 30:15.55.
[0057] Further, the mass ratio of the alkali-soluble bio-based resin to the first batch of fluorine-based acrylate monomers may be 30:(0.4-1.0), such as 30:0.41 or 30:0.97.
[0058] Further, the mass ratio of the alkali-soluble bio-based resin to the first batch of water may be 30:(250-300), for example, 30:259.9.
[0059] Furthermore, the mass ratio of the alkali-soluble bio-based resin to the second batch of non-fluorine-based vinyl monomers may be 30:(200-250), for example, 30:204.81 or 30:212.45.
[0060] Furthermore, the mass ratio of the alkali-soluble bio-based resin to the second batch of fluorine-based acrylate monomers may be 30:(5-15), for example, 30:5.59 or 30:13.03.
[0061] Further, the mass ratio of the alkali-soluble bio-based resin to the second batch of water may be 30:(100-150), for example, 30:120.10 or 30:123.18.
[0062] Furthermore, the raw material may further include an initiator. The initiator may be added in two batches, the first batch of initiators being added to the first raw material, and the second batch of initiators being added to the second raw material. The mass of the first batch of initiators may be 1%-20% of the mass of the alkali-soluble bio-based resin, for example, 1%. The mass of the second batch of initiators may be 5%-20% of the mass of the alkali-soluble bio-based resin, for example, 9% or 15.67%.
[0063] Furthermore, the raw material may also include an emulsifier. The emulsifier may be added in two batches, the first batch of emulsifier being added to the first raw material, and the second batch of emulsifier being added to the second raw material. The mass of the first batch of emulsifier may be less than 3% of the mass of the alkali-soluble bio-based resin, for example, 1.17% or 2.03%. The mass of the second batch of emulsifier may be less than 30% of the mass of the alkali-soluble bio-based resin, for example, 15.50% or 27.97%.
[0064] Furthermore, the raw material may further include a chain transfer agent. The chain transfer agent may be added to the second raw material. The mass of the chain transfer agent may be 2%-4% of the mass of the alkali-soluble bio-based resin, for example 4.13% or 2.69%.
[0065] In some specific embodiments, the initial temperature of the first polymerization reaction is 80-85°C, and the polymerization temperature during the second polymerization reaction is controlled to be 80-85°C.
[0066] In some specific embodiments, the initial temperature of the first polymerization reaction is 45-50°C, and the polymerization temperature during the second polymerization reaction is controlled to be no higher than 83°C.
[0067] Furthermore, the time of the first polymerization reaction can be based on the terminal temperature of the first polymerization reaction being 3° C. higher than the initial temperature of the polymerization reaction.
[0068] In a third aspect, the present invention provides an acrylate polymer emulsion prepared by the preparation method of the acrylate polymer emulsion as described above.
[0069] In a fourth aspect, the present invention provides a use of the acrylic polymer emulsion as described above as a decorative coating on a substrate.
[0070] In the present invention, the substrate may be a low surface tension substrate.
[0071] The surface tension of the low surface tension substrate may be no greater than 40 dyn / cm, for example 31-35 dyn / cm. In the present invention, the "surface tension" values are all surface tension values measured at 20°C.
[0072] Wherein, the low surface tension substrate can be a polypropylene substrate or a polyethylene substrate. The polyethylene substrate can be a PE film.
[0073] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0074] The reagents and raw materials used in the present invention are commercially available.
[0075] The positive and progressive effects of the present invention are:
[0076] (1) The acrylic polymer emulsion of the present invention contains an alkali-soluble bio-based resin and an acrylic polymer synthesized from monomers such as fluorinated acrylic esters; wherein the alkali-soluble bio-based resin can be used as a wetting agent in the acrylic polymer emulsion; the fluorine functional group on the carbon chain of the acrylic polymer increases the hydrophobicity of the acrylic polymer emulsion; the surface tension of the acrylic polymer emulsion is reduced to a level close to that of a low surface tension substrate, the contact area between the acrylic polymer emulsion and the substrate is increased, the distance between the polymer molecules and the molecules on the surface of the substrate is as close as possible, a larger intermolecular force is generated, and the peel strength of the acrylic polymer emulsion is improved;
[0077] (2) During the polymerization reaction of the present invention, the fluorine-based acrylate monomer undergoes a C=C addition reaction to graft the fluorine functional group onto the carbon chain of the acrylate polymer; while the non-fluorine-based vinyl monomer, fluorine-based acrylate monomer and water are added in batches, which makes it easy to remove the heat generated by the polymerization reaction and control the system stability of the acrylate polymer emulsion;
[0078] (3) In the present invention, the peel strength of the acrylic polymer emulsion on a low surface tension substrate can be ≥80 N / m, or even ≥95 N / m. DETAILED DESCRIPTION
[0079] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0080] In the following examples and comparative examples:
[0081] 1. Solid content refers to the mass percentage of solids in acrylic polymer emulsion. The specific test method is:
[0082] i. Instruments:
[0083] Electronic balance: d = 0.1 mg
[0084] Electric heating blast drying oven: constant temperature 140℃±2℃
[0085] Aluminum foil dish: Tin foil can be used instead
[0086] Glass vacuum desiccator: using color-changing silica gel as desiccant
[0087] ii. Measurement steps
[0088] (1) Seal the sample and place it at room temperature.
[0089] (2) Place a piece of tin foil on the scale and accurately record the weight: W c .
[0090] (3) Use a plastic pipette to transfer about 1g of sample into an aluminum foil dish (spread evenly without accumulation) and accurately record the weight: W w .
[0091] (4) Place the aluminum foil dish containing the weighed sample in an oven at a constant temperature of 140°C ± 2°C, start timing, take it out after 30 min ± 1 min, place it in a desiccator to cool to room temperature, weigh it, and record the weight: W d .
[0092] iii. Calculation results
[0093] The mass fraction of solid content is calculated according to formula (1), and the average value of two parallel measurements is calculated and the results are reported as the average value.
[0094] S=(W d -W c ) / (W w -W c )×100 (1)
[0095] Where:
[0096] S──solid content in the sample, %
[0097] W c ——The weight of the empty aluminum foil dish, g
[0098] W w ——The weight of the aluminum foil dish plus the sample before drying, g
[0099] W d ——The weight of the aluminum foil dish plus the sample after drying, g
[0100] 2. The viscosity test method of acrylic polymer emulsion is as follows: The viscosity test is based on the determination of liquid viscosity in GB / T22235-2008. Viscometer: NDJ-8S digital viscometer. Low temperature constant temperature bath: DC-3015. Viscosity measuring cup: 200ml, height 15cm, diameter 4.7cm. The specific steps include:
[0101] (1) Pour about 200 mL of sample into the viscosity measuring cup, cover and seal it. Do not allow air bubbles to enter. Place the beaker in a low-temperature thermostatic bath at 22°C ± 0.05°C to allow all parts of the sample to reach the required temperature of 22°C ± 0.1°C.
[0102] (2) Move the viscosity measuring cup after constant temperature into the LC-550MX constant temperature bath which has been kept at 22℃, and gently screw the rotor (select a rotor with a torque range of 40%-70%) onto the viscometer shaft. Note: When installing the rotor, the universal joint must be slightly lifted up to prevent damage to the rotating shaft tip.
[0103] (3) Rotate the nut to adjust the rotor height so that the rotor is placed in the center of the sample solution and the groove on the rotor is flush with the sample solution. Set the rotor number and speed.
[0104] (4) Use the viscometer temperature probe to confirm that the sample temperature reaches 22℃±0.1℃, press the "Run" key to start measurement.
[0105] (5) The measurement results are displayed directly on the screen and the readings are taken after stabilization.
[0106] 3. The test method for the average particle size of the acrylic polymer emulsion is as follows: using a Malvern nanoparticle size analyzer ZS-90, a certain amount of sample is dispersed in deionized water to prepare a solution with a mass fraction of 0.1% (the percentage is the mass ratio of the resin complex to the solution), ultrasonically oscillate for 3 minutes, and measure the average particle size using a nanoparticle size analyzer from Malvern Instruments, UK. The test is performed three times and the average value is taken.
[0107] Example 1
[0108] A method for preparing an acrylic polymer emulsion comprises the following steps:
[0109] a. Preparation of resin solution: Add 50g water and 30g peach gum into a reaction kettle, heat and mix, stir at a speed of 50 rpm, at a temperature of 80°C, and for 60min to obtain a colorless and transparent resin solution;
[0110] b. Preparation of pre-emulsion: 100 g of water, 180 g of methyl methacrylate, 40 g of butyl acrylate, 14 g of methyl 2-fluoroacrylate, 2 g of sodium dodecyl polyoxyethylene ether sulfate, and 3 g of OP-10 were added to a mixing kettle and mixed evenly, and allowed to stand for 2 hours without stratification to obtain a pre-emulsion;
[0111] c. Preparation of initiator solution: dissolve 3 g of ammonium persulfate in 30 g of deionized water to obtain an initiator solution;
[0112] d. Add 200g of deionized water into the reactor, add the resin solution (50g of water, 30g of peach gum) while stirring, and heat to 80-85°C;
[0113] e. Add 23.4 g of pre-emulsion (15.19 g of non-fluorinated monomer, 0.97 g of fluorinated monomer, 0.35 g of emulsifier, 6.90 g of water) and 3.3 g of initiator solution (0.3 g of initiator, 3 g of water) into the reactor;
[0114] f. When the temperature in the reactor rises by 3°C, add 0.808g of 2-mercaptoethanol into the reactor, and simultaneously begin to dropwise add the remaining initiator solution (2.7g of initiator, 27g of water) and the remaining pre-emulsion (204.81g of non-fluorinated monomer, 13.03g of fluorinated monomer, 4.65g of emulsifier, 93.10g of water). The dropping time is 2h, during which the reactor temperature is controlled at 80-85°C;
[0115] g. After the initiator solution and the pre-emulsified solution are added dropwise, keep warm for 1 hour;
[0116] h. Cooling and filtering the material to obtain an acrylate polymer emulsion, which includes water and a resin composite. The resin composite includes a mixture and / or a cross-linked product formed by peach gum and an acrylate polymer, has a solid content of 38.7%, a viscosity of 270 mPa·s, and a particle size of 77 nm.
[0117] Example 2
[0118] A method for preparing an acrylic polymer emulsion comprises the following steps:
[0119] a. Preparation of bio-based resin solution: 50 g of water and 30 g of sodium lignin sulfonate were added into a reaction kettle and heated and mixed at a stirring speed of 50 rpm, a temperature of 80°C, and a stirring time of 60 min to obtain a colorless and transparent solution;
[0120] b. Preparation of pre-emulsion: add 100g water, 140g methyl methacrylate, 88g butyl acrylate, 6g perfluorohexylethyl methacrylate, 3g sodium dodecylbenzenesulfonate, 4g OP-10 and 2g sodium perfluoroalkyl carboxylate into a mixing kettle and emulsify evenly, and let stand for 2 hours without stratification;
[0121] c. Preparation of initiator solution: dissolve 4.7 g of vitamin C in 30 g of deionized water to obtain an initiator solution;
[0122] d. Add 200 g of deionized water into the reactor, add the resin solution (50 g of water, 30 g of sodium lignin sulfonate) while stirring, and raise the temperature to 45-50 ° C;
[0123] e. Add 6 g of hydrogen peroxide (concentration 35 wt%), 0.001 g of ferrous sulfate, and 23.4 g of pre-emulsion (15.55 g of non-fluorinated monomer, 0.41 g of fluorinated monomer, 0.61 g of emulsifier, and 6.82 g of water) into the reactor;
[0124] f. When the temperature in the kettle rises by 3°C, add 1.24g of mercaptopropionic acid into the reactor, and simultaneously start to dropwise add initiator solution (4.7g initiator, 30g deionized water) and the remaining pre-emulsion (212.45g non-fluorine monomer, 5.59g fluorine monomer, 8.39g emulsifier, 93.18g water). The dropping time is 2h, and the temperature in the kettle rises naturally. During this period, the temperature of the reactor is controlled not to be higher than 83°C.
[0125] g. After the initiator solution and pre-emulsion solution are added dropwise, keep warm for 1 hour;
[0126] h. Cooling and filtering the material to obtain an acrylate polymer emulsion, which includes water and a resin composite. The resin composite includes a mixture and / or a cross-linked product formed by sodium lignin sulfonate and an acrylate polymer, has a solid content of 38.9%, a viscosity of 301 mPa·s, and a particle size of 83 nm.
[0127] Comparative Example 1
[0128] A method for preparing an acrylic polymer emulsion, compared with Example 1, the main difference is that peach gum is not added in this comparative example, and specifically comprises the following steps:
[0129] a. Preparation of pre-emulsion: 100 g of water, 180 g of methyl methacrylate, 40 g of butyl acrylate, 14 g of methyl 2-fluoroacrylate, 3 g of sodium dodecyl polyoxyethylene ether sulfate, and 4.5 g of OP-10 were added to a mixing kettle and emulsified evenly. The mixture was allowed to stand for 2 hours without stratification to obtain a pre-emulsion.
[0130] b. Preparation of initiator solution: dissolve 3 g of ammonium persulfate in 30 g of deionized water to obtain an initiator solution;
[0131] c. Add 230 g of deionized water into the reactor and heat to 80-85°C while stirring;
[0132] d. Add 23.4 g of pre-emulsion and 3.3 g of initiator solution into the reactor;
[0133] e. When the temperature in the reactor rises by 3°C, add 0.808 g of 2-mercaptoethanol into the reactor, and simultaneously begin to dropwise add the remaining initiator solution and the remaining pre-emulsion for 2 hours, during which the reactor temperature is controlled at 80-85°C;
[0134] f. After the initiator solution and pre-emulsified solution are added dropwise, keep warm for 1 hour;
[0135] g. Cooling the mixture and filtering the material to obtain an acrylic polymer emulsion having a solid content of 38.6%, a viscosity of 243 mPa·s and a particle size of 112 nm.
[0136] Comparative Example 2
[0137] A method for preparing an acrylic polymer emulsion, compared with Example 2, the main difference is that sodium lignin sulfonate is not added in this comparative example, and the method comprises the following steps:
[0138] a. Preparation of pre-emulsion: add 100g water, 140g methyl methacrylate, 88g butyl acrylate, 6g perfluorohexylethyl methacrylate, 6g sodium dodecylbenzenesulfonate, 4g OP-10 and 2g sodium perfluoroalkyl carboxylate into a mixing kettle and emulsify evenly, and let stand for 2 hours without stratification;
[0139] b. Preparation of initiator solution: dissolve 4.7 g of vitamin C in 30 g of deionized water to obtain an initiator solution;
[0140] c. Add 230 g of deionized water into the reactor and heat to 45-50°C while stirring;
[0141] d. Add 6 g of hydrogen peroxide (concentration 35 wt%), 0.001 g of ferrous sulfate, and 23.4 g of pre-emulsion into the reactor;
[0142] e. When the temperature in the kettle rises by 3°C, add 1.24g of mercaptopropionic acid into the reactor, and start dripping the initiator solution and the remaining pre-emulsion at the same time. The dripping time is 2h. The temperature in the kettle rises naturally. During this period, the temperature of the reactor is controlled not to be higher than 83°C.
[0143] f. After the initiator solution and pre-emulsion solution are added, keep warm for 1 hour;
[0144] g. Cooling and filtering the material to obtain an acrylate polymer emulsion, wherein the acrylate polymer emulsion includes water and a resin composite, wherein the resin composite includes a mixture and / or a cross-linked product formed by sodium lignin sulfonate and an acrylate polymer, has a solid content of 38.6%, a viscosity of 271 mPa·s, and a particle size of 117 nm.
[0145] Effect Example 1: Peel Strength Test
[0146] 1. Samples to be tested: Acrylate polymer emulsions in Examples 1-2 and Comparative Examples 1-2
[0147] 2. Test method: Take 20g of sample and apply it evenly on 200mm×30mm PE film with cotton pad. After the coating is dry, repeat the application for 3 times, with a total of 60g sample. Stick it vertically on 20mm wide 3M tape and use a tensile machine to test the 90° peel strength (test temperature is 20±5℃, relative humidity <80%). The specific parameters of the tensile machine are: speed 50mm / min, displacement 50mm, and effective test width 20mm.
[0148] Effect Example 2: System Stability
[0149] 1. Samples to be tested: Acrylate polymer emulsions in Examples 1-2 and Comparative Examples 1-2
[0150] 2. Test method: Take 500g of sample and place it in a transparent glass bottle, cover the bottle cap tightly, place it in a 40℃ oven for 7 days, and observe whether there is stratification or precipitation.
[0151] The test results of the acrylic polymer emulsions of Examples 1-2 and Comparative Examples 1-2 are shown in Table 1.
[0152] Table 1
[0153]
[0154] According to the comparison between Example 1 and Comparative Example 1, peach gum is not added to the acrylic polymer emulsion of Comparative Example 1, and the peel strength declines significantly while the solid content remains almost unchanged, and the stability becomes worse.
[0155] According to the comparison between Example 2 and Comparative Example 2, sodium lignin sulfonate is not added to the acrylic polymer emulsion of Comparative Example 2, and the peel strength decreases significantly while the solid content remains almost unchanged, and the stability becomes worse.
Claims
1. An acrylic polymer emulsion, characterized in that: It includes water and a resin compound, wherein the resin compound includes a mixture and / or a crosslinked product formed by an alkali-soluble bio-based resin and an acrylate polymer; wherein the content of each component is: Water 40%-70%, Alkali soluble bio-based resin 4%-15%, Acrylate polymer 10.5%-65%; The percentage is the percentage of each component to the total mass of the acrylic polymer emulsion; The acrylic ester polymer comprises a repeating unit I corresponding to a non-fluorine-based vinyl monomer and a repeating unit II corresponding to a fluorine-based acrylic ester monomer, and the mass ratio of the repeating unit I to the repeating unit II is (10-60):(0.5-5).
2. The acrylic acid ester polymer emulsion according to claim 1, characterized in that The alkali-soluble bio-based resin is one or more of peach gum, shellac and sodium lignin sulfonate; And / or, the non-fluorinated vinyl monomer is one or more of methyl methacrylate, acrylonitrile, butyl acrylate, isooctyl acrylate and styrene; And / or, the fluorinated acrylate monomer is one or more of 2-fluoromethyl acrylate, perfluorohexylethyl methacrylate and perfluoroalkylethyl methacrylate; And / or, the solid content of the acrylic polymer emulsion is 35%-40%, such as 38.7% or 38.9%, where the solid content refers to the mass percentage of solids in the acrylic polymer emulsion; and / or, the viscosity of the acrylic polymer emulsion is 280-320 mPa·s, such as 270 mPa·s or 301 mPa·s; And / or, the average particle size of the acrylic polymer emulsion is 75-85 nm, such as 77 nm or 83 nm.
3. The acrylic polymer emulsion according to claim 1, characterized in that The resin composite meets the following conditions ① or ②: ① The alkali-soluble bio-based resin is peach gum, and the fluorine-based acrylate monomer is 2-fluoromethyl acrylate; the mass ratio of the peach gum to the repeating unit II is 30:(10-15), for example, 30:14; ② The alkali-soluble bio-based resin is sodium lignin sulfonate, and the fluorinated acrylate monomer is perfluorohexylethyl methacrylate; the mass ratio of the sodium lignin sulfonate to the repeating unit II is 30:(5-10), for example 30:
6.
4. A method for preparing an acrylic polymer emulsion, characterized in that: It includes the following steps: The raw materials are subjected to polymerization reaction to obtain; Wherein, the raw material includes the following components: Alkali soluble bio-based resin 4%-15%; Polymer monomer 10.5%-65%; Water 40%-70%; The percentage is the percentage of the mass of each component to the total mass of the raw material; The polymer monomers include a non-fluorine-based vinyl monomer and a fluorine-based acrylate monomer, and the mass ratio of the non-fluorine-based vinyl monomer to the fluorine-based acrylate monomer is (10-60):(0.5-5); During the polymerization reaction, the alkali-soluble bio-based resin is added all at once, and the polymer monomer and the water are added in batches.
5. The method for preparing the acrylic polymer emulsion according to claim 4, characterized in that: The alkali-soluble bio-based resin is one or more of peach gum, shellac and sodium lignin sulfonate; and / or, the mass of the alkali-soluble bio-based resin is 4.0%-5.0% of the total mass of the raw material, such as 4.51% or 4.60%; And / or, the alkali-soluble bio-based resin and water are added after forming a resin solution; preferably, the method for preparing the resin solution comprises: mixing the alkali-soluble bio-based resin and water, heating, and stirring; the heating temperature is preferably 70-80° C.; the stirring speed is preferably 50-80 r / min; the stirring time is preferably 30-60 min; And / or, the non-fluorinated vinyl monomer is one or more of methyl methacrylate, acrylonitrile, butyl acrylate, isooctyl acrylate and styrene; And / or, the mass of the non-fluorinated vinyl monomer is 30%-40% of the total mass of the raw materials, such as 33.7% or 34.3%; And / or, the fluorinated acrylate monomer is one or more of 2-fluoromethyl acrylate, perfluorohexylethyl methacrylate and perfluoroalkylethyl methacrylate; And / or, the mass of the fluorinated acrylate monomer is 0.80%-3.00% of the total mass of the raw materials, such as 0.90% or 2.14%; And / or, the raw material further includes an emulsifier; preferably, the mass of the emulsifier is less than 5% of the total mass of the raw material, for example, 0.77%-1.35%; preferably, the emulsifier is a non-fluorinated emulsifier and / or a fluorinated emulsifier; the fluorinated emulsifier is preferably a perfluoroalkyl carboxylate and / or a perfluoroalkyl amide; the perfluoroalkyl carboxylate is preferably a sodium salt of a perfluoroalkyl carboxylate or a potassium salt of a perfluoroalkyl carboxylate; the perfluoroalkyl amide is preferably perfluorooctane sulfonamide; The non-fluorine emulsifier is preferably one or more of sodium dodecyl polyoxyethylene ether sulfate, sodium dodecylbenzene sulfonate and OP-10; wherein the mass of the fluorine emulsifier is preferably less than 2% of the total mass of the raw materials; the mass of the non-fluorine emulsifier is preferably less than 3% of the total mass of the raw materials; preferably, the polymer monomer is added after forming a pre-emulsion with the emulsifier and water; the adding method is preferably dropwise addition; preferably, the emulsifier is added in batches; And / or, the raw material further includes an initiator; the initiator is preferably one or more of potassium persulfate, sodium persulfate, ammonium persulfate, hydrogen peroxide, ferrous sulfate, vitamin C and sodium pyrosulfite; the mass concentration of H2O2 in the hydrogen peroxide is preferably 7.5%-35%; preferably, the mass of the initiator is 0.1%-3.0% of the total mass of the raw material; preferably, the initiator and water are added after forming an initiator solution, and the adding method is preferably dropwise addition; preferably, the initiator is added in batches; And / or, the raw material also includes a chain transfer agent; preferably, the chain transfer agent is one or more of 2-mercaptoethanol, thioglycolic acid, mercaptopropionic acid and isopropanol; preferably, the mass of the chain transfer agent is 0.1%-3.0% of the total mass of the raw material, for example, 0.12%-0.19%; the chain transfer agent is preferably added after the alkali-soluble bio-based resin is added.
6. The method for preparing the acrylic acid ester polymer emulsion according to claim 4, characterized in that: The polymerization reaction satisfies the following conditions ① or ②: ① The initial temperature of the polymerization reaction is 80-85°C, and the polymerization temperature is controlled to be 80-85°C during the polymerization reaction; ② The initial temperature of the polymerization reaction is 45-50°C, and the polymerization temperature is controlled not to be higher than 83°C during the polymerization reaction.
7. The method for preparing the acrylic acid ester polymer emulsion according to claim 4, characterized in that: The polymer monomer is added in two batches, and the preparation method of the acrylic ester polymer emulsion comprises the following steps: S1, subjecting a first raw material to a first polymerization reaction; the first raw material comprises an alkali-soluble bio-based resin, a first batch of non-fluorine-based vinyl monomers, a first batch of fluorine-based acrylate monomers and a first batch of water; S2, subjecting the second raw material to a second polymerization reaction; the second raw material comprises the reaction product of step S1, a second batch of non-fluorine-based vinyl monomers, a second batch of fluorine-based acrylate monomers, and a second batch of water; The mass ratio of the alkali-soluble bio-based resin to the first batch of non-fluorine-based vinyl monomers is preferably 30:(15-16), such as 30:15.19 or 30:15.55; the mass ratio of the alkali-soluble bio-based resin to the first batch of fluorine-based acrylate monomers is preferably 30:(0.4-1.0), such as 30:0.41 or 30:0.97; the mass ratio of the alkali-soluble bio-based resin to the first batch of water is preferably 30:(250-300), such as 30:259.9; The mass ratio of the alkali-soluble bio-based resin and the second batch of non-fluorine-based vinyl monomers is preferably 30:(200-250), such as 30:204.81 or 30:212.45; the mass ratio of the alkali-soluble bio-based resin and the second batch of fluorine-based acrylate monomers is preferably 30:(5-15), such as 30:5.59 or 30:13.03; the mass ratio of the alkali-soluble bio-based resin and the second batch of water is preferably 30:(100-150), such as 30:120.10 or 30:123.18; The raw materials preferably further include an initiator; the initiator is preferably added in two batches, the first batch of initiators is added to the first raw material, and the second batch of initiators is added to the second raw material; the mass of the first batch of initiators is preferably 1%-20% of the mass of the alkali-soluble bio-based resin, for example 1%; the mass of the second batch of initiators is preferably 5%-20% of the mass of the alkali-soluble bio-based resin, for example 9% or 15.67%; The raw material preferably further includes an emulsifier; the emulsifier is preferably added in two batches, the first batch of emulsifier is added to the first raw material, and the second batch of emulsifier is added to the second raw material; the mass of the first batch of emulsifier is preferably less than 3% of the mass of the alkali-soluble bio-based resin, such as 1.17% or 2.03%; the mass of the second batch of emulsifier is preferably less than 30% of the mass of the alkali-soluble bio-based resin, such as 15.50% or 27.97%; The raw material preferably further includes a chain transfer agent; the chain transfer agent is added to the second raw material; the mass of the chain transfer agent is preferably 2%-4% of the mass of the alkali-soluble bio-based resin, for example 4.13% or 2.69%; Preferably, the initial temperature of the first polymerization reaction is 80-85°C, and the polymerization temperature during the second polymerization reaction is controlled to be 80-85°C; Preferably, the initial temperature of the first polymerization reaction is 45-50°C, and the polymerization temperature during the second polymerization reaction is controlled not to be higher than 83°C; The time of the first polymerization reaction is preferably based on the terminal temperature of the first polymerization reaction being 3° C. higher than the initial temperature of the polymerization reaction.
8. An acrylic ester polymer emulsion prepared by the method for preparing an acrylic ester polymer emulsion according to any one of claims 4 to 7.
9. Use of the acrylic polymer emulsion according to any one of claims 1 to 3 and 8 as a decorative coating for a substrate.
10. The use of the acrylic polymer emulsion according to claim 9, characterized in that: The surface tension of the substrate is not greater than 40 dyn / cm, for example 31-35 dyn / cm; And / or, the substrate is a polypropylene substrate or a polyethylene substrate; the polyethylene substrate is preferably a PE film.